Digital Literacy asan Indicator of Adolescent Mental Health and Implementation for the Role of School Counselor : A Systematic Literature Review - Nur Mega, Aris Saputra; Muslihati, A.; M. Ramli, M.; Ahmad Yusuf, Sobri; Amalia, Madihie; Fifi Khoirul, Fitriyah (Uphills Publishers LLC, Sheridan, United States, 2024)
The impact of problematic social media leads to mental health tendencies experienced by teenagers. One of the skills that teenagers are pioneering in using social media is digital literacy skills. The tendency for low levels of digital literacy among teenagers is very likely to be correlated with the mental health conditions of teenagers. This research aims to describe the correlation of digital literacy as an indicator of adolescent mental health and how role of school counselors. This research method is asystematic literature review with the search keywords "digital literacy"; "adolescent mental health"; "digital literacy and mental health" on the ScienceDirect, Sage, Taylor and Francis platforms. The results of the identification resulted in 14 articles which were studied in depth and resulted in the finding that digital literacy skills contributed to the mental health conditions of teenagers. Digital literacy is a link between teenagers and the digital world which will have an impact on mental health. Implementation of prevention and intervention is carried out by school counselors to prevent the impact of adolescent mental health problems.